Optical coating technology - Baumeister, Philip (SPIE monograph, 2004)
Baumeister organizes this book around the key subjects associated with functions of optical thin film performance, and provides a valuable resource in the field of thin film technology. The information is widely backed up with citations to patents and published literature. The author draws from 25 years of experience teaching classes at the UCLA Extension Program, and at companies worldwide to answer questions, such as: what are the conventions for a given analysis formalism? and, what other design approaches have been tried for this application?